Early definitive treatment rate as a quality indicator of care in acute gallstone pancreatitis. Issue 12 (9th August 2017) - Green, R; Charman, S C; Palser, T
Abstract: Background: Early definitive treatment (cholecystectomy or endoscopic sphincterotomy in the same admission or within 2 weeks after discharge) of gallstone disease after a biliary attack of acute pancreatitis is standard of care. This study investigated whether compliance with early definitive treatment for acute gallstone pancreatitis can be used as a care quality indicator for the condition. Methods: A retrospective cohort study was conducted using the Hospital Episode Statistics database. All emergency admissions to National Health Service hospitals in England with a first time diagnosis of acute gallstone pancreatitis in the financial years 2008, 2009 and 2010 were examined. Trends in early definitive treatment between hospital trusts were examined and patient morbidity outcomes were determined. Results: During the study interval there were 19 510 patients with an overall rate of early definitive treatment at 34·7 (range 9·4–84·7) per cent. In the 1-year follow-up period, 4661 patients (23·9 per cent) had one or more emergency readmissions for complications related to gallstone pancreatitis. Of these, 2692 (57·8 per cent) were readmissions for acute pancreatitis; 911 (33·8 per cent) were within the first 2 weeks of discharge, with the remaining 1781 (66·2 per cent) occurring after the point at which definitive treatment should have been received. Early definitive treatment resulted in a 39 per cent reduction in readmission risk (adjusted risk ratio (RR) 0·61, 95 per cent c.i. 0·58 to 0·65). The risk was further reduced for acute pancreatitis readmissions to 54 per cent in the early definitive treatment group (adjusted RR 0·46, 0·42 to 0·51). Conclusion: In acute gallstone pancreatitis, compliance with recommended early definitive treatment varied considerably, with associated variation in outcomes. Compliance should be used as a quality indicator to improve care. Abstract : Variation in compliance relates to outcomes